INTERNET-BASED LEARNING: TRANSFORMING EDUCATION IN THE DIGITAL AGE (Modern education and development, 2025)
The proliferation of the internet has revolutionized various sectors, and education is no exception. Internet-based learning, often referred to as online learning or e-learning, has emerged as a transformative force, providing accessible and flexible education opportunities to learners worldwide. This article explores the benefits, challenges, and future potential of internet-based learning, supported by academic insights and data.